Sequential implantations of deuterium and helium ions into tungsten-coated composite structures - Azarenkov, N.A.; Bobkov, V.V.; Tishchenko, L.P.; Starovoitov, R.I.; Kovtunenko, Yu.I.; Logachev, Yu.E.; Gamayunova, L.A. (Вопросы атомной науки и техники, 2016)
The trapping and thermal desorption of deuterium and helium implanted into tungsten-coated composite structures were studied. The amount of accumulated deuterium and helium, and the shape of thermal desorption spectra were shown to be depended on the way of irradiation by the D⁺ and He⁺ ions: individually or sequentially. The possible mechanisms of these processes are proposed. Изучены процессы захвата и термической десорбции дейтерия и гелия, имплантированных в композиционные структуры с вольфрамовым покрытием. Количества накопленных дейтерия и гелия и вид спектров термической десорбции показаны в зависимости от схемы облучения ионами D⁺ и He⁺ : по отдельности или последовательно в разной очерёдности. Предложены возможные механизмы этих процессов. Вивчено процеси захоплювання та термічної десорбції дейтерію та гелію, імплантованих у композиційні структури з вольфрамовим покриттям. Кількості накопичених дейтерію та гелію та вигляд спектрів термічної десорбції показано в залежності від схеми опромінення іонами D⁺ та He⁺ : окремо або послідовно в різній черговості. Запропоновані можливі механізми цих процесів.